1995
DOI: 10.1182/blood.v86.12.4681.bloodjournal86124681
|View full text |Cite
|
Sign up to set email alerts
|

Induction of tolerance in nondefective mice after in utero transplantation of major histocompatibility complex-mismatched fetal hematopoietic stem cells

Abstract: Significant morbidity and mortality are associated with the conditioning therapy needed for postnatal bone marrow transplantation (BMT) for inherited diseases. This could be eliminated with hematopoietic stem cell (HSC) transplantation in utero, when the immunoincompetence of the fetus permits engraftment without the need for immunosuppressive therapy. We have established an in utero (day 11 to day 13) model of HSC transplantation in nondefective, allogeneic major histocompatibility complex (MHC)-mismatched mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(64 citation statements)
references
References 20 publications
5
59
0
Order By: Relevance
“…Hence, histocompatibility matching, immunosuppression, and myeloablation are not necessary for successful prenatal transplantation. 16 Rapid expansion and proliferation of the developing fetal hematopoietic compartment provides space for the engraftment of circulating stem cells. Therefore, the therapeutic potential of in utero hematopoietic stem cell (HSC) transplantation is based on the unique opportunity provided by normal hematopoietic ontogeny.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, histocompatibility matching, immunosuppression, and myeloablation are not necessary for successful prenatal transplantation. 16 Rapid expansion and proliferation of the developing fetal hematopoietic compartment provides space for the engraftment of circulating stem cells. Therefore, the therapeutic potential of in utero hematopoietic stem cell (HSC) transplantation is based on the unique opportunity provided by normal hematopoietic ontogeny.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed engraftment of donor HSCs and reconstitution of normal hematopoiesis after IUT into fetal mice in the W/Wv locus, creating severe combined immunodeficient (SCID) and nondefective murine models. 16,[28][29][30][31] The purpose of this study was to investigate the feasibility of xenogenic IUT of human BM-MSCs into normal, immunocompetent fetal mice.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic chimerism after in utero transfer of allogeneic hematopoietic cells has been demonstrated in a variety of large and small animal models [12,14,17,20,22,25,31,39,47]. Unlike the high levels of chimerism (10-50%) that are noted in naturally occurring hematopoietic chimeras the level of chimerism in most animal models and human clinical attempts has been low (<1%).…”
Section: Discussionmentioning
confidence: 99%
“…18 The occurrence of GVHD is related purely to T-cell dose and complete T-cell depletion increases the rate of failure of engraftment. Allogeneic engraftment has also been demonstrated in the normal fetal primate, 19 goat, 20 and mouse 21 following in utero transplantation.…”
Section: Experimental Support For In Utero Hsc Transplantationmentioning
confidence: 96%